Correlation between computed tomography volumetry and nuclear medicine split renal function in live kidney donation: a single‐centre experience. Issue 7 (21st June 2020) - Hua, Lina; Sebben, Ruben; Olakkengil, Santosh; Russell, Christine; Coates, Toby; Bhattacharjya, Shantanu
Abstract: Background: Potential live renal donors undergo both renal computed tomography angiogram (CTA) and nuclear imaging dimercaptosuccinic acid (DMSA) scans. Each kidney's renal function and vascular anatomy influences the choice of donor side. Although DMSA measures differential blood flow, it is a surrogate for renal function and nephron mass. Computed tomography techniques can provide volumetry information. The aim of this study was to determine the relationship between measured split renal volumes on computed tomography versus renal volumes derived from DMSA split function in live donors. Methods: Prospective data of live kidney donors assessed at a single Australian centre from 2014 to 2017 were reviewed. All patients had pre‐operative CTA and DMSA imaging. Renal volume was determined via semi‐automated software calculation from CTA three‐dimensional image reconstructions by one investigator. Measured split renal volume was compared against calculated renal volume using measured DMSA split function (percentage split function multiplied by total renal volume). Results: Fifty‐three patients were included in the study. Split renal volumes on three‐dimensional CTA images correlate to calculated split volumes determined from DMSA (Pearson coefficient 0.95 for right renal volume, 0.95 for left). The decision of which kidney to remove can be achieved with CTA only. Omitting a DMSA scan would reduce the radiation load by 0.70 mSv (35 chest X‐rays) and potential cost saving of AU1062.00 per donor. Conclusion: CTA technology allows accurate assessment of renal volumes that correlate well with DMSA split function. Avoiding a DMSA scan results in cost and radiation reduction in the assessment of a live kidney donor. Abstract : Current computed tomography technology allows accurate assessment of renal volumes that correlate well with dimercaptosuccinic acid split function. The decision of which kidney to donate is based on function and anatomy which can be achieved with a computed tomography angiogram only.